2006
DOI: 10.1215/15228517-2006-008
|View full text |Cite
|
Sign up to set email alerts
|

The role of human glioma-infiltrating microglia/macrophages in mediating antitumor immune responses1

Abstract: Little is known about the immune performance and interactions of CNS microglia/macrophages in glioma patients. We found that microglia/macrophages were the predominant immune cell infiltrating gliomas ( approximately 1% of total cells); others identified were myeloid dendritic cells (DCs), plasmacytoid DCs, and T cells. We isolated and analyzed the immune functions of CD11b/c+CD45+ glioma-infiltrating microglia/macrophages (GIMs) from postoperative tissue specimens of glioma patients. Although GIMs expressed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
444
3
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 537 publications
(485 citation statements)
references
References 77 publications
(69 reference statements)
32
444
3
6
Order By: Relevance
“…This finding is interesting because it differs from all imaging studies with [ 11 C](R)-PK11195 [11], microarray studies [5], studies in vitro [27,28], animal model [3,29,30] and post-mortem brains [22] that showed high expression of PBR in activated microglia in a variety of inflammatory, degenerative, infective and vascular CNS disorders. Our approach of combining the evaluation of PBR using [ 11 C](R)-PK11195 PET-scan and immunohistochemistry offered the advantage of studying the binding capacity of this molecule in vivo and, on tissues its distribution in the cell types constituting the two astrocytomas without the changes that may occur examining microglia in vitro, outside the complexity of interactions with other cell types [5]. In addition, these two cases represented a rare opportunity and an excellent model to investigate microglial PBR because they showed low-PBR expression in neoplastic cells and minimal contrast enhancement indicating minimal disruption of the blood brain barrier and therefore little presence of blood-borne macrophages within tumour tissue.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…This finding is interesting because it differs from all imaging studies with [ 11 C](R)-PK11195 [11], microarray studies [5], studies in vitro [27,28], animal model [3,29,30] and post-mortem brains [22] that showed high expression of PBR in activated microglia in a variety of inflammatory, degenerative, infective and vascular CNS disorders. Our approach of combining the evaluation of PBR using [ 11 C](R)-PK11195 PET-scan and immunohistochemistry offered the advantage of studying the binding capacity of this molecule in vivo and, on tissues its distribution in the cell types constituting the two astrocytomas without the changes that may occur examining microglia in vitro, outside the complexity of interactions with other cell types [5]. In addition, these two cases represented a rare opportunity and an excellent model to investigate microglial PBR because they showed low-PBR expression in neoplastic cells and minimal contrast enhancement indicating minimal disruption of the blood brain barrier and therefore little presence of blood-borne macrophages within tumour tissue.…”
Section: Discussionmentioning
confidence: 82%
“…These findings elicit an intriguing hypothesis on the role of PBR in microglial immune functions. The PBR is one of the most common molecules expressed by microglial cells during activation but its role in these cells is unknown and the molecular pathway linking the functions of PBR to microglial response has not been elucidated [5]. In a mouse model, Banati et al [42] showed that PBR is up-regulated at the early stages of activation when microglial cells still show a ramified morphology and suggested that PBR may be a key molecule in microglial immune response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations